Coordniation of center of mass velocity and upper extremity kinematics during basketball shots from two distances - Wiens, C.; McNitt-Gray, J. (ISBS Proceedings Archive (Michigan), 2021)
The purpose of this study was to analyze the coordination patterns for individual players when shooting from different distances. Seven experienced basketball players attempted at least 10 shots from 4.19 m and 6.02 m from the hoop. The coordination between the player`s center of mass vertical velocity, upper arm angular velocity, and forearm angular velocity were characterized using phase-plane analysis. Within player, coordination of center of mass vertical velocity and arm kinematics were found to be unique to each individual and comparable between shot distances, particularly during the shot preparation phase. Deviations in coordination patterns between shot distances were attributed to increases in center of mass vertical velocity at ground departure and ball release, consistent with the need for a greater ball velocity at release at further shot distances.